Map of the United States, and territories. Together with Canada &c. - Williams, W. (Wellington) (S. Augustus Mitchell, Jr., 1879)
Map shows the boundary between United States and Mexico according to the treaty of 1848 and the Gadsden Treaty of 1854, boundaries between "Dacotah" Territory and Wyoming, Indian Territory, mail routes, "Route to Santa Fe," major cities, and areas of Native American habitation. Inset: "Island of Newfoundland." Relief shown by hachures. Scale [ca. 1:10,140,000].